Men’s perspectives on the impact of femaledirected cash transfers on gender relations: Findings from the HPTN 068 qualitative study - Makhosazane Nomhle Khoza; Sinead Delany-Moretlwe; Fiona Scorgie; Jennifer Hove; Amanda Selin; John Imrie; Rhian Twine; Kathleen Kahn; Audrey Pettifor; Catherine MacPhail (My University, 2018)
Background HIV is an inherently gendered disease in eastern and southern Africa, not only because more women than men are infected, but also because socially constructed gender norms work to increase women’s HIV-infection risk. The provision of cash transfers to young women alone in such a context adds another dimension to already existing complex social relations where patriarchal values are entrenched, gender inequality is the norm, and violence against women and girls is pervasive. It raises concerns about complicating young women’s relationships with their male partners or possibly even setting them up for more violence. In our attempt to understand how cash transfers influence social relations in the context of a trial among young women in South Africa, we used qualitative data collected during the trial to explore men’s perceptions of the impact of cash transfers on male-female relationships, both intimate and platonic, peer relationships. Method Between April 2012 and August 2015, we conducted focus group discussions (n = 12) and interviews (n = 20) with the male peers and intimate partners of young women aged 13–20 years, who were participating in a phase III randomised controlled trial of CTs for HIV prevention in Mpumalanga, South Africa. A thematic content analysis approach was used to analyse the data. The codebook was developed on the basis of the topic guides, with additional codes added inductively as they emerged from the data. Results Intimate partners were older (range 20–32 years) and more likely to be working than the male peers. Both intimate partners and male peers were supportive of the CT trial targeting young women; younger peers however expressed some concerns that the money might diminish their power and status in relationships. HIV testing requirements associated with the trial appeared to have improved communication about sex and HIV in intimate relationships, with some women even encouraging their partners to go for an HIV test. Conclusion CTs provide AGYW with a measure of autonomy and power to contribute in their gendered relationships, albeit in limited ways. However, there is potential for CTs to have a negative impact on male-female relationships if the cash received by AGYW is equal to or greater than the income earned by their male counterparts or sexual partners.